Analysis of Factors Influencing Technology Adoption to Increase MSME Productivity in Malang City - SARI, Rizqi Aprilia; KORNITASARI, Yenny (Journal of Tourism Economics and Policy, 2024)
This study aims to analyze the factors influencing technology adoption by Micro, Small, and Medium Enterprises (MSMEs) in Malang City during the digitalization era, using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) as the theoretical framework. Data were collected from 100 MSME respondents in Malang City and analyzed using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) method. The UTAUT2 model was applied to examine the influence of performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, and habit on technology adoption and productivity. The findings indicate that performance expectancy, facilitating conditions, and habit have a significant positive impact on productivity, highlighting the importance of efficiency, infrastructure support, and consistent technology usage. Conversely, effort expectancy, social influence, and hedonic motivation do not significantly affect technology adoption. The study emphasizes the need for policymakers and stakeholders to enhance digital infrastructure, provide technology training, and offer incentives to increase technology adoption among MSMEs. These strategies are expected to strengthen competitiveness, foster innovation, and drive sustainable economic growth in Malang City.